Menggugat Netralitas Hukum Pidana: Perdebatan Ideologis di Balik Kebijakan Kriminal di Negara-Negara Liberal - Zul Khaidir Kadir (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
A number of liberal countries, such as the United States, England, Germany, and Sweden, have legal systems that claim to uphold the principles of democracy and human rights. However, in practice, there are more complex political dynamics. Behind the seemingly neutral codification of criminal law, there are ideological influences that are often invisible to the naked eye. This study uses a normative legal research method with a comparative approach. Data collection was collected using library research, then analyzed qualitatively and presented descriptively. The results of the study show that from the analysis of criminal policy in the United States, England, Germany, and Sweden, it is clear that criminal law not only functions as a mechanism for enforcing justice, but also as an instrument that reflects and responds to political and social dynamics in each country. Although each country has a different context and approach, there are common patterns that can be seen in criminal policy in these countries. Criminal law not only functions to uphold justice objectively, but also becomes an arena where political ideology, public fears, and social challenges meet and shape policies that ultimately affect the lives of millions of people.